KINERJA KEUANGAN DAN NILAI PERUSAHAAN PEMBELAJARAN DARI PERUSAHAAN SEKTOR CONSUMER CYCLICAL DI BURSA EFEK INDONESIA - Porajow, Mc Donald (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract: This research aims to examine the influence of financial performance using profitability, liquidity, and solvency ratios on company value, providing an overview of investor behavior towards the current capital conditions of the market in Indonesia and wants to examine signal information about financial performance and prove that it is directly related to company value. This research uses secondary data by taking samples from companies in the consumer cyclical sector listed on the Indonesia Stock Exchange in 2020-2023. This research used a purposive sampling method, the number of samples obtained was 41 samples. The data obtained were analyzed using multiple linear regression with the PLS SEM 4.0 statistical tool. The research results show that there is no influence of Profitability, Liquidity, and Solvency on Company value Keywords: Financial Performance, Profitability, Liquidity, Solvency, Company Value